Is earlier obesity associated with poorer executive functioning later in childhood? Findings from the Millennium Cohort Study. Issue 9 (16th March 2021) - Creese, Hanna‐Marie; Hope, Steven; Christie, Deborah; Goddings, Anne‐Lise; Viner, Russell
Summary: Background: Children affected with overweight or obesity have been associated with having lower educational achievement compared to peers who are non‐overweight/obese. One of the drivers of this association could be a link between obesity and poorer executive function. Evidence is limited to small, cross‐sectional studies which lack adjustment for important common causes. Objective: We investigate the association between weight status and executive function longitudinally in mid‐childhood, accounting for potential common causes. Methods: Linear regression analyses were conducted to examine associations between weight status between 5 and 7 years and executive functioning at 11 years in members of the Millennium Cohort Study ( n  = 7739), accounting for a wide range of potential common causes. Age‐ and sex‐specific International Obesity Taskforce cut‐points for body mass index (BMI) were used. Executive function, including decision‐making, impulsivity and spatial working memory, was assessed using the Cambridge Neuropsychological Test Automated Battery. Results: There were no unadjusted associations between weight status and decision‐making or impulsivity. After adjustment for all potential common causes, there was a lack of consistent evidence to support an association between persistent obesity (including overweight) between 5 and 7 years and spatial working memory task at 11 years. Conclusions: We found little evidence that poorer spatial working memory contributes to the association of children with obesity having lower educational achievement.